2020
DOI: 10.1111/cpf.12668
|View full text |Cite
|
Sign up to set email alerts
|

Impulse oscillometry and spirometry measurements relative to personal best values at the time of acute exacerbations of cystic fibrosis in adults

Abstract: Background Diagnosis of acute exacerbation (AE) of cystic fibrosis (CF) must be precise because both under‐ and over‐prescription of antibiotics may be detrimental. How lung function tests contribute to diagnose AE is unclear. We aimed to describe variation of spirometry and oscillometry measurements, at Stable state and at AE in adults with CF. Methods Patients were included in a retrospective single‐centre study when both spirometry (FEV1, FVC) and oscillometry (X5, R5, R5−R20 and AX) data were available for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
(56 reference statements)
2
5
0
Order By: Relevance
“…Annual Data Report as well as the United Kingdom Cystic Fibrosis Registry Annual Data Report 2019 (18,185). The average FEV1 in our study was 63% predicted, which was also very similar to reported values in 3 of the recent publications that examined oscillometry in adult CF (141,143,144).…”
Section: Univariable Multivariablesupporting
confidence: 91%
See 3 more Smart Citations
“…Annual Data Report as well as the United Kingdom Cystic Fibrosis Registry Annual Data Report 2019 (18,185). The average FEV1 in our study was 63% predicted, which was also very similar to reported values in 3 of the recent publications that examined oscillometry in adult CF (141,143,144).…”
Section: Univariable Multivariablesupporting
confidence: 91%
“…With respect to oscillometry, both resistance and reactance parameters were abnormal compared to population-based reference values (84). The average R5 and R5-20 values were generally comparable to those recently obtained in adults with CF by other investigators where these parameters were in fact measured (see Table 11) (141)(142)(143)(144). The average X5 was close to that reported by Lima et al (141) and Wallaert et al (142), while the average AX and Fres were very similar to that observed by Lima et al (141).…”
Section: Univariable Multivariablesupporting
confidence: 81%
See 2 more Smart Citations
“…IOS may provide objective information that is beneficial to patients whose spirometry is either normal or could not be performed; thus, the comparisons of spirometric and IOS data in the same patients with several types of lung diseases have received growing interest. [25][26][27] R5-R20, X5, Fres, and Ax in the patients were measured in the current study; these conventional IOS parameters have been suggested to detect airway obstruction. 9,10 For example, R5-R20 is a measure of the peripheral airway resistance that is determined mainly by airway caliber.…”
Section: Discussionmentioning
confidence: 93%